The role of composite dietary antioxidants in elderly cognitive function: insights from NHANES - Chen, Fangsen; Chen, Junhan; Liu, Peitian; Huang, Yanling (Frontiers in Nutrition, 2024)
Objective: This study investigates the relationship between the Composite Dietary Antioxidant Index (CDAI) and cognitive function among elderly individuals, aiming to understand how increased antioxidant intake affects cognitive abilities in an aging population. Methods: Utilizing data from the National Health and Nutrition Examination Survey (NHANES) from 2011-2014, we analyzed a sample of 2,516 participants aged 60 and above. Cognitive performance was assessed using the CERAD Word Learning and Recall Test, the Animal Fluency Test, and the Digit Symbol Substitution Test. Multivariable regression models were adjusted for demographic, dietary, and health-related factors to explore the association between CDAI scores and cognitive outcomes. Results: The regression analyses showed a statistically significant positive association between higher CDAI scores and cognitive performance across several tests. Specifically, increments in CDAI were associated with increased scores in the CERAD Word Learning Test: Score 1 (β=0.04, 95% CI [0.03, 0.06]), Score 2 (β=0.04, 95% CI [0.02, 0.05]), Score 3 (β=0.04, 95% CI [0.02, 0.06]), and the Delayed Recall Test (β=0.04, 95% CI [0.01, 0.06]). Additionally, significant improvements were observed in the Animal Fluency Test (β=0.19, 95% CI [0.14, 0.24]) and the Digit Symbol Test (β=0.55, 95% CI [0.39, 0.71]). Subgroup analyses further highlighted that higher CDAI scores conferred more pronounced cognitive benefits in women, individuals aged 80 and above, Non-Hispanic black people, and those with lower educational levels, suggesting that dietary antioxidants might be particularly beneficial in these groups. Conclusion: An antioxidant-rich diet may represent a viable intervention to mitigate age-related cognitive decline, supporting cognitive health in the elderly. These results underscore the potential public health implications of dietary recommendations aimed at increasing antioxidant consumption among older adults. Further studies are necessary to confirm these findings and to investigate the underlying mechanisms in detail.